2019
DOI: 10.1021/acssynbio.9b00026
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Rewiring Improves the Production of the Fungal Active Targeting Molecule Fusarinine C

Abstract: Author: Recently, increasing research in siderophores has been dedicated to their possible medical applications in diagnostics and therapeutics for human pathogenic infections. Fusarinine C (FsC) is a natural hydroxamate siderophore that harbors three amino groups, which allow the easy chemical modification of FsC for the design of novel multifunctional conjugates. However, low production of FsC has hampered its extensive exploitation.Herein, we rewired the FsC biosynthetic pathway in the Aureobasidium melanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In A. melanogenum, siderophore biosynthesis is the only known metabolic pathway that uses N 5 -hydroxy-L-ornithine as the precursor (Lu et al, 2019a(Lu et al, ,2019b. Previously, we reported that the biosynthesis of ferricrocin and hydroxyferricrocin siderophores in the recombined A. melanogenum strain DOLC19 was eliminated through the deletion of the L-ornithine-N 5transacetylase gene sidL and the FC synthase gene sidC (Lu et al, 2019a(Lu et al, ,2019b; however, the biosynthesis of fusarinine C (FsC) and FsC-derived fusarinine B (FsB) siderophores was still active. To completely block the consumption of N 5 -hydroxy-L-ornithine through the biosynthesis of FsC and FsB in the DOLC19 strain, the first genetic manipulation was the deletion of the anhydromevalonyl-CoA transferase gene sidF, which converts N 5 -hydroxy-L-ornithine into FsC (Hu et al, 2019) (Fig.…”
Section: Elimination Of Siderophore Biosynthesis To Develop a Chassis Strainmentioning
confidence: 99%
See 3 more Smart Citations
“…In A. melanogenum, siderophore biosynthesis is the only known metabolic pathway that uses N 5 -hydroxy-L-ornithine as the precursor (Lu et al, 2019a(Lu et al, ,2019b. Previously, we reported that the biosynthesis of ferricrocin and hydroxyferricrocin siderophores in the recombined A. melanogenum strain DOLC19 was eliminated through the deletion of the L-ornithine-N 5transacetylase gene sidL and the FC synthase gene sidC (Lu et al, 2019a(Lu et al, ,2019b; however, the biosynthesis of fusarinine C (FsC) and FsC-derived fusarinine B (FsB) siderophores was still active. To completely block the consumption of N 5 -hydroxy-L-ornithine through the biosynthesis of FsC and FsB in the DOLC19 strain, the first genetic manipulation was the deletion of the anhydromevalonyl-CoA transferase gene sidF, which converts N 5 -hydroxy-L-ornithine into FsC (Hu et al, 2019) (Fig.…”
Section: Elimination Of Siderophore Biosynthesis To Develop a Chassis Strainmentioning
confidence: 99%
“…1B, Module 1), yielding SidF-null strain DF1. After the DF1 strain was cultivated in an iron-depleted (modified sucrose peptone; MSP) medium (Lu et al, 2019a(Lu et al, ,2019b for 120 h, high-performance liquid chromatography (HPLC) analysis showed that none of the characteristic peaks of FsC and FsB siderophores produced by the DOLC19 strain (Fig. S1A) could be detected in the fermentation broth of the DF1 strain (Fig.…”
Section: Elimination Of Siderophore Biosynthesis To Develop a Chassis Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, M. thermautotrophicus NifB generated NifX that contained in vivo formed NifB-co. [62] The FeMo (NifDK) tetramer and the active Fe protein from P. polymyxa WLY78 werep roduced in the cytoplasm of S. cerevisiae by expressing a1 5-genen itrogenase biosynthetic pathway ( % 38 kb). [63] Of the 15 genes, 11 genes (nifH, nifD, nifK, nifB, nifE, nifN, nifV, nifX, hesA, groES, groEL)w ere from P. polymyxa WLY78 and 4g enes (nifF, nifJ, nifS, nifU)w ere from K. oxytoca. Each coding region of the 15 genes was codon optimized for S. cerevisiae and then fused with ay east promoter and a yeast terminator,g enerating 15 expressionc assettes.…”
Section: Engineering Nitrogen Fixation In Yeast (Saccharomyces Cerevimentioning
confidence: 99%